Grotesque visions - Haakenson, Thomas O., 1972- (New York, NY : Bloomsbury Academic, 2021)
"Grotesque Visions focuses on the radical avant-garde interventions of Salomo Friedländer (aka Mynona), Til Brugman, and Hannah Höch as they challenged the questionable practices and evidentiary claims of late-19th- and early-20th-century science. Demonstrating the often excessive measures that pathologists, anthropologists, sexologists, and medical professionals went to present their research in a seemingly unambiguous way, this volume shows how Friedländer/Mynona, Brugman, Höch, and other Berlin-based artists used the artistic grotesque to criticize, satirize, and subvert a variety of forms of supposed scientific objectivity. The volume concludes by examining the exhibition Grotesk!: 130 Jahre Kunst der Frechheit/Comic Grotesque: Wit and Mockery in German Arts, 1870-1940. In contrast to the ahistorical and amorphous concept informing the exhibition, Thomas O. Haakenson reveals a unique deployment of the artistic grotesque that targeted specific established and emerging scientific discourses at the turn of the last fin-de-siècle"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Grotesque in art; Grotesque in literature; Science in art; Science in literature; Avant-garde (Aesthetics) -- Germany -- Berlin -- History; German literature -- 20th century -- History and criticism; Literature, Experimental -- Germany -- Berlin -- History and criticism; Grotesque dans l'art.; Grotesque dans la littérature.; Sciences dans l'art.; Sciences dans la littérature.; Littérature allemande -- 20e siècle -- Histoire et critique; Littérature expérimentale -- Allemagne -- Berlin -- Histoire et critique; Avant-garde (Aesthetics); German literature; Grotesque in art; Grotesque in literature; Literature, Experimental; Science in art; Science in literature; Germany -- Berlin; 1900-1999; Criticism, interpretation, etc; History